Analytical methods for food and dairy powders / [electronic resource] - Schuck, Pierre; Dolivet, Anne.; Jeantet, Romain (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2012)
Food and dairy powders are created by dehydrating perishable produce, such as milk, eggs, fruit and meat, in order to extend their shelf life and stabilise them for storage or transport. These powders are in high demand for use as ingredients and as food products in their own right, and are of great economic importance to the food and dairy industry worldwide. Today, the ability to control food and dairy powder quality is a source of key competitive advantage. By varying the dehydration process design, and by controlling the technological and thermodynamic parameters during dehydration, it is.
Front Matter -- Colour Plates -- Dehydration Processes and their Influence on Powder Properties -- Determination of Dry Matter and Total Dry Matter -- Determination of Nitrogen Fractions -- Determination of the Rate of Lactose Crystallisation -- Determination of Total Fat and Free Fat Content -- Determination of the Ash Content -- Determination of Particle Size and Friability -- Determination of Flowability and Floodability Indices -- Determination of Density, Interstitial Air Content and Occluded Air Content -- Determination of Colour and Appearance -- Determination of the Sorption Isotherm, Water Activity and Hygroscopicity of Powders -- Determination of Glass Transition Temperature Range -- Determination of Rehydration Ability -- Summary and General Conclusion -- Index.
Includes bibliographical references and index.
Online resource; title from title screen (viewed Feb. 27, 2012).
Keywords: Food -- Analysis; Food -- Composition; Dairy products -- Drying; TECHNOLOGY & ENGINEERING -- Food Science; Dairy products -- Drying; Food -- Analysis; Food -- Composition; Electronic books